1994
DOI: 10.1161/01.atv.14.3.471
|View full text |Cite
|
Sign up to set email alerts
|

Plasma essential fatty acids, cigarette smoking, and dietary antioxidants in peripheral arterial disease. A population-based case-control study.

Abstract: The aim of this study was to determine the levels of plasma fatty acids in patients with peripheral arterial disease and in control subjects and to identify whether any risks of disease related to these differences were influenced by smoking and antioxidant intake. A random sample of 1592 men and women aged 55 to 74 years was selected from the general population (the Edinburgh Artery Study), from which 153 cases of peripheral arterial disease were identified by the presence of intermittent claudication and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 34 publications
(31 reference statements)
1
37
2
Order By: Relevance
“…Food groups have been examined in relation to PAD in few previous studies, although associations between dietary intake of nutrients and PAD have been studied more extensively (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In a large sample of adults who completed vascular screening tests, nut consumption was inversely associated with prevalent PAD (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food groups have been examined in relation to PAD in few previous studies, although associations between dietary intake of nutrients and PAD have been studied more extensively (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In a large sample of adults who completed vascular screening tests, nut consumption was inversely associated with prevalent PAD (20).…”
Section: Discussionmentioning
confidence: 99%
“…Several dietary factors support a strong causal link with coronary artery disease, including the protective effect of the Mediterranean diet, a high-quality diet, a "prudent" diet, vegetables, and nuts and the harmful effect of the "Western" diet, trans-fatty acids, and high-glycemic index or load (5). Crosssectional and case-control studies have suggested that PAD is inversely associated with several nutrients, including fiber from cereal (6)(7)(8), vegetable oil (9), vitamin A (8, 10), vitamin C (8,(11)(12)(13), vitamin D (14)(15)(16), vitamin E (7-9, 13), and folate (8,10,(17)(18)(19), although the relation may not be causal. Recent research on dietary patterns and food groups has found that increased nut intake is cross-sectionally associated with lower PAD prevalence (20), whereas higher meat consumption has been associated with a lower mean ankle-brachial index (ABI) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of meat rather than fish generally leads to increased consumption of DPA (Howe, Meyer, Record, & Baghurst, 2006), although the implications of this in relation to CVD risk are not clear. One study (Leng et al, 1994) compared subjects with peripheral arterial disease (case) with healthy controls and found that plasma EPA, DPA and DHA concentrations were all significantly lower in the cases than in control subjects, but only DPA showed a relationship with the disease independent of smoking and only DPA reduced the risks associated with smoking. Also Sun et al (2008) showed that higher plasma EPA and DPA (but not DHA) concentrations were associated with a lower risk of nonfatal myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Besides heart disease, stroke prevention and arterial blockage also comprise a significant part of cardiovascular health. Plasma levels of DPA are inversely related to blocked arteries and DPA the only n-3 fatty acid that has been shown to significantly reduce blocked arteries regardless of lifetime smoking 45 . A cross-sectional study with carotid ultrasonography revealed that carotid artery wall thickness was inversely associated with DPA intake 46 .…”
Section: Potential Clinical Effects Of Dpamentioning
confidence: 95%